Pengaruh Permainan Tradisional Karetan Terhadap Pembelajaran Motorik Kasar Atletik Lompat Jauh - Ratna Nila Puspitasari (Universitas Trunojoyo Madura, 2016)
Research on Child elementary school class 1 Bulukidul District of Balong Ponorogo motivated by lower gross motor skills long jump. This is evident from a minimum completeness criteria child has not reached the KKM. The aim of this study is to demonstrate the influence of traditional games, learning karetan Rough Motoric athletics long jump first graders in elementary school Bulukidul Balong Ponorogo.This study uses a quantitative research approach to the type of quasi-experimental and research design Nonequivalen Control Group Design. The population in this study were grade 1 primary school children Bulukidul Balong Ponorogo. The sample used is the number of the population of 34 children were divided into two groups: the experimental group and the control group were selected randomly based rombel learning. Data were analyzed using non-parametric statistical test of Mann-Whitney U-Test.Based on the analysis of data between the experimental group and the control group in the long jump, the obtained prices U1 value of the experimental group was smaller than the control group U2. With an error rate of 0.05 by the number n1 = 17 and n2 = 17 obtained table 77, the price of U count is smaller than the U table so Ho rejected and Ha accepted